2021
DOI: 10.3390/biom11020291
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genotoxicity Attributed to Diesel Exhaust Particles in Normal Human Embryonic Lung Cell (WI-38) Line

Abstract: Several epidemiological studies concluded that inhalation of diesel exhaust particles (DEP) is associated with an increase in the relative risk of lung cancer. In vitro research evaluating the genetic damage and/or changes in gene expression have been attempted to explain the relationship between DEP exposure and carcinogenicity. However, to date, investigations have been largely confined to studies in immortalized or tumorigenic epithelial cell models. Few studies have investigated damage at the chromosomal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Both environmental and engineered NMs have been shown to induce adverse health effects, such as pulmonary, cardiovascular, neurological, and reproductive disorders [ 6 , 7 , 8 ]. A direct association between exposure to diesel exhaust particles (DEPs) in exhaust fumes and lung cancer has been demonstrated [ 9 , 10 , 11 , 12 ]. Engineered NMs, (e.g., metallic nanoparticles, quantum dots, carbon nanotubes) have also been shown to cause toxicity after inhalation exposure [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both environmental and engineered NMs have been shown to induce adverse health effects, such as pulmonary, cardiovascular, neurological, and reproductive disorders [ 6 , 7 , 8 ]. A direct association between exposure to diesel exhaust particles (DEPs) in exhaust fumes and lung cancer has been demonstrated [ 9 , 10 , 11 , 12 ]. Engineered NMs, (e.g., metallic nanoparticles, quantum dots, carbon nanotubes) have also been shown to cause toxicity after inhalation exposure [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous reports, DEPs induce genotoxicity in normal human embryonic lung cells, and its potential inhibitory effects on cell cycle progression through RNA expression have been noted [40,41]. First, to confirm the cytotoxicity of 9,10-PQ in HeLa cells, we treated the cells with 1, 2, 4, or 8 µM 9,10-PQ for up to 24 h, in agreement with the methods of a previous study [16], and examined the cell morphology, viability, and protein expression (Figure S1A-C).…”
Section: Exposure To 910-pq Disturbs Mitotic Progressionmentioning
confidence: 99%
“…Based on epidemiological evidence indicating DEP’s association with an increase in the relative risk of lung cancer, Lee et al [ 3 ] attempted to study the genotoxic effects of DEP at the chromosomal level using normal embryonic human lung fibroblast cells with micronuclei (MN) and comet assays. They found that DEP exposure induced DNA damage at the chromosomal level in normal human lung cells and provided information on the expression of genes associated with genotoxic stress.…”
mentioning
confidence: 99%